Price cap regulation in the Colombian pharmaceutical market: An impact evaluation (2021)
We evaluate the impact of a price cap regulation implemented in the Colombian pharmaceutical market between 2011 and 2014. To do so, we take advantage of a unique data set where we observe three sources of variation: i) differences across eighteen groups in the Anatomical Therapeutic Chemical (ATC) classification system of the WHO, ii) the existence of regulated (treated) and unregulated (control) groups within each of these eighteen ATC groups, and iii) differences in time (before and after regulation) for the eighteen ATC groups. A triple differences model with Fixed time effects and cluster errors is used to identify the impact of this regulation. We Find that the price-cap regulation contributed to reduce prices in three of the eighteen groups and increase average prices for ten of them. We confirm then that the focal point effect generated by a price-cap regulation can generate unintended distortions. More specifically, our results reveal that the implementation of this price cap regulation potentially increased -public and private- expenditure by 30%, only for the 2,422 drugs in the eighteen ATC groups we study.